Extraction of Chlorophyll from Pandan Wangi Leaves (Pandanus amaryllifolius Roxb.) as Natural Textile Dyes - Nila Tanyela Berghuis; Lania Ameswari Isnaeni; Karisma Nur Shaleha; Aninda Tri Kusumaningrum; Erma Maryana; Fitri Kurniawati (Universitas Sultan Ageng Tirtayasa, 2024)
This research focuses on the utilization of natural materials such as textile dyes, which are environmentally friendly and safe for the health of living things. The natural ingredients used are pandan wangi leaves (Pandanus amaryllifolius Roxb.), especially chlorophyll compounds, which are green pigments. The types of fabrics tested consisted of cotton fabrics, linen fabrics, and drill fabrics. The purpose of this study was to extract chlorophyll from pandan wangi leaves via the maceration extraction method with ethanol and maceration for 36 hours. The particle size of the pandan wangi leaves was made up to 60 mesh to obtain the optimum extraction yield. Fabric coloring begins by washing the fabric with Turkish Red Oil (TRO) solution and then mordanting it with various concentrations of 1% and 0.6% alum mordant. Fabrics that have been dyed are then tested for color fastness to sunlight and rubbing. The results of maceration of the ethanol extract produced a yield value of 40.22%. The chlorophyll a and b contents were calculated from the absorbance values obtained via ultraviolet‒visible (UV‒Vis) spectroscopy, namely, 3.7223 µg/mL and 1.1362 µg/mL, respectively. Fourier transform infrared (FTIR) characterization revealed the presence of methyl, ketone, amine, and ester functional groups. The values of the test results for color fastness to sunlight and rubbing were 4 (good) and 4‒5 (very good), respectively.